Life milestones and psychological visions of Ivan Chetverykov - PREDKO, Denys; LEVCHENKO, Yuliya (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2025)
Background. Despite the emergence of studies devoted to the history of Ukrainian psychology during the years of Ukraine's independence, many personalities, and their activities and teachings, remain unknown to both the scientific community and the general public. Ivan Chetverykov is one such personality.Results. The article is centered on the autobiographical narrative and ideas of the Ukrainian educator and psychologist I. Chetverykov. The study emphasizes the analysis of his biography, professional career, and contributions to the development of psychology, pedagogy, and social science. It also highlights the methodological foundations of his works. The main directions of I. Chetverykov's psychological studies are outlined, particularly the humanistic approach (viewing psychology as a tool for understanding the individual uniqueness of each person); the connection between the concept of God as a subject with personal characteristics (consciousness, will, emotions, and capacity for interaction) and the formation and development of human personality; and the psychology of love (love being not only an emotional or cultural phenomenon but also an intrinsic component of human nature rooted in attachment needs and evolutionary stimuli). In exploring the relationship between the Person and God, I. Chetverykov focused on the dialogic nature of this relationship. According to the thinker, dialogue is not only an act of faith but also a pathway to a fulfilling life and personal improvement.Conclusions. The main dimensions of I. Chetverykov's educational, pedagogical, and scientific endeavors, particularly the religious and personal psychological dimensions, are identified and their role in the formation of national psychology is articulated.
Keywords: psychology; history of psychology; I. Chetverykov; methodology; psychology of love; personality of God; dialog between personality and God